2020
DOI: 10.1007/s11214-019-0629-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and Pulsating Aurora

Abstract: This chapter reviews fundamental properties and recent advances of diffuse and pulsating aurora. Diffuse and pulsating aurora often occurs on closed field lines and involves energetic electron precipitation by wave-particle interaction. After summarizing the definition, large-scale morphology, types of pulsation, and driving processes, we review observation techniques, occurrence, duration, altitude, evolution, small-scale structures, fast modulation, relation to high-energy precipitation, the role of ECH wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 203 publications
(286 reference statements)
6
93
0
Order By: Relevance
“…A recent study by Hosokawa and Ogawa (2015) showed a higher European Incoherent Scatter (EISCAT) electron density at lower altitudes during PsA, which is more pronounced in the morning sector. Similarly, Oyama et al (2016) showed a maximum electron density below 100 km during a pulsating aurora. Jones et al (2009) utilized ionization from incoherent scatter radar in Poker Flat, Alaska, to estimate the energy distribution of PsA electrons and compared it with rocket measurements.…”
Section: Introductionmentioning
confidence: 88%
“…A recent study by Hosokawa and Ogawa (2015) showed a higher European Incoherent Scatter (EISCAT) electron density at lower altitudes during PsA, which is more pronounced in the morning sector. Similarly, Oyama et al (2016) showed a maximum electron density below 100 km during a pulsating aurora. Jones et al (2009) utilized ionization from incoherent scatter radar in Poker Flat, Alaska, to estimate the energy distribution of PsA electrons and compared it with rocket measurements.…”
Section: Introductionmentioning
confidence: 88%
“…Pulsating auroras (PsAs) are caused by the intermittent precipitation of electrons with energies ranging from a few kiloelectron volts to ~100 keV from the magnetosphere to the upper atmosphere (e.g., Miyoshi et al, 2010; Sandahl et al, 1980; Yau et al, 1981). Lower‐band chorus (LBC) waves cause the precipitation of these electrons through pitch angle scattering (e.g., Jaynes et al, 2013; Jones et al, 2009; Kasahara et al, 2018; Lessard, 2012; Miyoshi et al, 2010; Nishimura et al, 2010, 2020). Miyoshi, Saito et al (2015) have proposed a model to describe the relationship between the energy spectrum of the precipitating electrons in PsA and the frequency spectrum of LBC.…”
Section: Introductionmentioning
confidence: 99%
“…The diffuse aurora is a frequent source of high‐energy precipitating electron and is the dominant source of total auroral energy flux (Newell et al, 2009; Nishimura et al, 2020). Consisting of higher energy particles than its counterpart, the discrete aurora, the diffuse aurora is largely observed in the equatorward portion of the auroral oval (Nishimura et al, 2020). The nightside diffuse aurora is strongest in the early morning sector, with the region of strongest energy flux centered on 3 h magnetic local time (MLT) (Newell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to EUV photoionization, both Pedersen and Hall conductivities also receive contributions from precipitating electrons (Vickrey et al, 1981). However, in the E region ionosphere, Hall conductivity peaks at a lower altitude than Pedersen conductivity, making Hall conductance more susceptible to deeply penetrating precipitating electrons and thus to higher energy electrons (Coumans et al, 2004; Nishimura et al, 2020). In fact, when considering high‐latitude Hall conductance, auroral precipitation has a greater impact than EUV photoionization (Lotko et al, 2014).…”
Section: Introductionmentioning
confidence: 99%